Electrochemical performance of composites made of rGO with Zn-MOF and PANI as electrodes for supercapacitors. (20th January 2021) - Quoc Bao, Le; Nguyen, Thanh-Huong; Fei, Haojie; Sapurina, Irina; Ngwabebhoh, Fahanwi Asabuwa; Bubulinca, Constantin; Munster, Lukas; Bergerová, Eva Domincová; Lengalova, Anezka; Jiang, Hao; Trong Dao, Tran; Bugarova, Nikola; et al.
Abstract: Metal-organic frameworks (MOFs) have lately obtained great attention of scientists as potential materials applied for supercapacitor electrodes. Due to their crystalline structure, MOFs show proper electrochemical double-layer capacitance at the enlarged specific surface area of the material and the mechanical supports for the composite materials. In this study, Zn-MOF was synthesized and composited with reduced graphene oxide (rGO) to be applied as a supercapacitor electrode material. To improve the electrodes working performance, polyaniline (PANI) was synthesized by different methods and added to the composite. The electrochemical properties of these materials were studied to identify the effect of PANI and Zn-MOF on the electrode materials. Among the composites obtained, the best specific capacitance of about 372 F/g was obtained at 0.1 A/g charge-discharge analysis of rGO/Zn-MOF@PANI sample due to its large surface with high pores sizes. The capacitance retentions of electrodes were also tested to decipher the effect caused by varied composites fabrication. Graphical abstract: Image, graphical abstract